Evaluating apprenticeship training programs for firms - Samuel Mühlemann; Harald Pfeifer (IZA World of Labor, 2023)
Apprenticeship training programs typically last several years and require substantial investments by training firms, largely due to the associated labor costs for participants and instructors. Nevertheless, apprentices also add significant value in the workplace. One tool to measure the costs and benefits of training for firms is employer surveys, which were first introduced in the 1970s in Germany. Such cost-benefit surveys (CBS) help to better understand a firm's demand for apprentices and to identify market failures. Therefore, CBS are an important tool for designing effective training policies.
Keywords: J23; J24; J32; M53; 330; apprenticeship and firm-sponsored training; cost-benefit surveys; return to training investment; human capital